8 Surfaces Invariant by One-Parameter Group of Hyperbolic Isometries Having Constant Mean Curvature in ˜ PSL2(R,Τ)

8 Surfaces Invariant by One-Parameter Group of Hyperbolic Isometries Having Constant Mean Curvature in ˜ PSL2(R,Τ)

8 Surfaces invariant by one-parameter group of hyperbolic isometries having constant mean curvature in PSL2(R,τ) g On (3) Ricardo Sa Earp gave explicit formulas for parabolic and hyper- bolic screw motions surfaces immersed in H2 R. There, they gave several × examples. In this chapter we only consider surfaces invariant by one-parameter group of hyperbolic isometries having constant mean curvature immersed in P] SL (R, τ). Since for τ 0 we are in H2 R then we have generalized the result 2 ≡ × obtained by Ricardo Sa Earp when the surface is invariant by one-parameter group of hyperbolic isometries having constant mean curvature. In this chapter we focus our attention on surfaces invariant by one- parameter group of hyperbolic isometries. To study this kind of surfaces, we take M 2 = H2 that is the half plane model for the hyperbolic space. Thus, the metric of M 2 is given by: 1 dσ2 = λ2(dx2 + dy2), λ = . y From Proposition 5.1.1, we know that to obtain a hyperbolic motion on ] P SL2(R, τ), it is necessary consider a hyperbolic motion (hyperbolic isometry) on H2. 8.1 Surfaces invariant by one-parameter group of hyperbolic isometries main lemma The idea to obtain a surface invariant by one-parameter group of hyper- bolic isometries is simple, we will take a curve in the xt plane and we will apply ] one-parameter group Γ of hyperbolic isometries on P SL2(R, τ). We denote by α(x)=(x, 1,u(x)) the curve in the xt plane and by S = Γ(α), the surface invariant by one-parameter group of hyperbolic isometries generate by α. Since the most simple hyperbolic isometry on H2 is the homotetia from the origin, we re-parameterized the hyperbolic plane whit coordinates R+ and Surfaces of Constant Mean Curvature in Homogeneous Three Manifolds with ] Emphasis in PSL2(R, τ) 124 θ (0, π), so that ∈ x = R cos(θ) y = R sin(θ) where R R and θ (0, π). ∈ ∈ Thus, the surface S is parameterized by, ϕ(ρ, θ)=(R cos(θ), R sin(θ),u(θ)) Now, we rewrite all the expressions in this news coordinates, thus we obtain the next lemma. Lemma 8.1.1. By considering the above re-parametrization to the hyperbolic plane, we may rewrite all terms in the form, sin(θ) – ∂ = cos(θ)∂ ∂ x R − R θ cos(θ) – ∂ = sin(θ)∂ + ∂ y R R θ – Rx = cos(θ) – Ry = sin(θ) sin(θ) – θ = x − R cos(θ) – θ = y R 1 – λ = R sin(θ) 1 – dσ2 = (dR2 + R2dθ2) R2 sin2(θ) Proof. From, x = R cos(θ), (8-1) ( y = R sin(θ), we obtain, dx = cos(θ)dR R sin(θ)dθ, − (8-2) ( dy = sin(θ)dR + R cos(θ)dθ, since, dx2 + dy2 = dR2 + R2dθ2, 1 λ = R sin(θ) Surfaces of Constant Mean Curvature in Homogeneous Three Manifolds with ] Emphasis in PSL2(R, τ) 125 1 then λ2 = , thus, R2 sin2(θ) dσ2 = λ2(dx2 + dy2) 1 = dR2 + R2dθ2 R2 sin2(θ) Furthermore, setting ∂x = a∂R + b∂θ and evaluating in equation (8-2). We obtain, 1 = cos(θ)a R sin(θ)b, − ( 0 = sin(θ)a + R cos(θ)b, hence, sin(θ) a = cos(θ), b = − R that is, sin(θ) ∂ = cos(θ)∂ ∂ . x R − R θ By considering, ∂y = a∂R + b∂θ and evaluating in equation (6-2). We obtain, 0 = cos(θ)a R sin(θ)b, − ( 1 = sin(θ)a + R cos(θ)b, so cos(θ) a = sin(θ), b = R that is, cos(θ) ∂ = sin(θ)∂ + ∂ . y R R θ From x2 + y2 = R2, we obtain, 2x = 2RRx 2y = 2RRy Considering the equation (8-1), we obtain, Rx = cos(θ) Ry = sin(θ) Surfaces of Constant Mean Curvature in Homogeneous Three Manifolds with ] Emphasis in PSL2(R, τ) 126 Derivation of equation (8-1) with respect to x and y respectively gives, 1= R cos(θ) R sin(θ)θ x − x 1= Ry sin(θ)+ R cos(θ)θy Now, by using Rx and Ry, we obtain, sin(θ) θ = x − R cos(θ) θ = y R This completes the proof. The next Lemma is crucial for our study. We follow ideas of Appendix A of (11). Consider the graph t = u(θ) in the plane xt, and denote by S = grap(Γu). Supposing that S has constant mean curvature H, we have the lemma: Lemma 8.1.2. The function u satisfies (d 2H cot(θ)) 1+4τ 2 cos2(θ) u(θ)= − dθ 2τθ (8-3) 1 sin2(θ)(d 2H cot(θ))2 − Z − p− where d is a real number.p Proof. Since S has mean curvature H, then by lemma 5.2.1 the function u satisfies the equation α β 2H = divH2 e + e , (8-4) W 1 W 2 u u where W = 1+ α2 + β2, α = x 2τ, and β = y . λ − λ p By abuse of notation we consider u(x, y)= u(R(x, y), θ(x, y)), since S is a surface invariant by one-parameter group of hyperbolic isometries, then the function u does not depend of R, so, ux = uRRx + uθθx = uθθx, ( uy = uRRy + uθθy = uθθy, Surfaces of Constant Mean Curvature in Homogeneous Three Manifolds with ] Emphasis in PSL2(R, τ) 127 By considering the lemma 8.1.1, this implies, u x = u sin2(θ) λ − θ u y = u sin(θ) cos(θ) λ θ Thus α = u sin2(θ) 2τ − θ − β = uθ sin(θ) cos(θ) this implies, 2 2 2 2 2 2 α + β = sin (θ)(uθ +2τ) +4τ cos (θ) 2 2 2 2 2 W = 1 + sin (θ)(uθ +2τ) +4τ cos (θ) α β 1 ∂ ∂ Setting X = e + e = α x + β y . u W 1 W 2 W λ λ We need express Xu in coordinates R and θ. Observe that, ∂ x = R sin θ cos θ∂ sin2 θ∂ λ R − θ and ∂ y = R sin2 θ∂ + sin θ cos θ∂ λ R θ Furthermore, ∂ ∂ α x + β y = (sin2 θu +2τ)(R sin θ cos θ∂ sin2 θ∂ )+ λ λ − θ R − θ 2 + sin θ cos θuθ(R sin θ∂R + sin θ cos θ∂θ) = [R sin3 θ cos θu +2τR sin θ cos θ]∂ + [sin4 θu +2τ sin2 θ]∂ − θ R θ θ 3 2 2 +R sin θ cos θuθ∂R + sin θ cos θuθ∂θ = 2τR sin θ cos θ∂ + sin2 θ(u +2τ)∂ − R θ θ So, we conclude that, 1 X = sin2 θ(u +2τ)∂ 2τR sin θ cos θ∂ u W θ θ − R and 2 2 2 2 W = 1+4τ cos θ + sin θ(uθ +2τ) q Surfaces of Constant Mean Curvature in Homogeneous Three Manifolds with ] Emphasis in PSL2(R, τ) 128 Let θ , θ (0, π) with θ < θ and R , R R+ with R < R and 0 1 ∈ 0 1 0 1 ∈ 0 1 consider the domain Ω = [θ , θ ] [R , R ] in the plane R+θ. 0 1 × 0 1 η3 γ3 θ1 γ4 η2 Ω η4 γ 2 θ0 γ1 η1 R0 R1 By integrating the equation (8-4), we obtain X , η =2HArea([θ , θ ] [R , R ]) h u i 0 1 × 0 1 Z∂(Ω) where η is the outer co-normal. Since X , η = X , η + X , η + X , η + X , η h u i h u 1i h u 2i h u 3i h u 4i Z∂Ω Zγ1 Zγ2 Zγ3 Zγ4 we compute each integral: For the fist integral: Observe that, γ (s)=(s, θ ), R s R . 1 0 0 ≤ ≤ 1 This implies, γ1′ = ∂R, thus 1 γ′ = , | 1| R sin θ and η = sin θ∂ . 1 − θ Furthermore sin3 θ(u +2τ)(θ ) 1 sin θ(u +2τ) X , η = θ 0 = θ , h u 1i − W sin2 θ − W Surfaces of Constant Mean Curvature in Homogeneous Three Manifolds with ] Emphasis in PSL2(R, τ) 129 hence R1 u +2τ X , η = θ (θ )dR h u 1i − RW 0 Zγ1 ZR0 For the third integral: Observe that, γ (s)=(R s, θ ), 0 s R R . 3 1 − 1 ≤ ≤ 1 − 0 This implies, γ′ = ∂ , 3 − R thus 1 γ′ = , | 3| R sin θ and η3 = sin θ∂θ. Furthermore sin3 θ(u +2τ)(θ ) 1 sin θ(u +2τ) X , η = θ 1 = θ , h u 3i W sin2 θ W hence, R1 R0 R1 − sin θ(u +2τ) 1 (u +2τ) X , η = θ ds = θ (θ )dR h u 3i W (R s) sin θ RW 1 Zγ3 Z0 1 − ZR0 For the second integral: Observe that, γ (s)=(R ,s), θ s θ . 2 1 0 ≤ ≤ 1 This implies, γ2′ = ∂θ, thus 1 γ′ = , | 2| sin θ and η2 = R sin θ∂R. Furthermore 2τR2 sin2 θ cos θ 1 2τ cos θ X , η = = , h u 2i − W R2 sin2 θ − W Surfaces of Constant Mean Curvature in Homogeneous Three Manifolds with ] Emphasis in PSL2(R, τ) 130 hence, θ1 2τ cos θ X , η = dθ h u 2i − W sin θ Zγ2 Zθ0 For the four integral: Observe that, γ (s)=(R , θ s), 0 s θ θ . 4 0 1 − ≤ ≤ 1 − 0 This implies, γ′ = ∂ , 4 − θ thus 1 γ′ = , | 4| sin θ and η = R sin θ∂ . 4 − R Furthermore 2τR2 sin2 θ cos θ 1 2τ cos θ X , η = = , h u 4i W R2 sin2 θ W hence, θ1 θ0 θ1 − 2τ cos(θ s) 1 2τ cos θ X , η = 1 − ds = dθ h u 4i W sin(θ s) W sin θ Zγ4 Z0 1 − Zθ0 Taking into account this four integrals, we obtain R1 (u +2τ) dR R1 (u +2τ) dR X , η = θ (θ ) θ (θ ) h u i W 1 R − W 0 R Z∂Ω ZR0 ZR0 Observe that, θ1 R1 Area(Ω) = det(gij)dRdθ θ0 R0 Z Z q θ1 R1 1 = dRdθ R sin2 θ Zθ0 ZR0 So, we conclude that R1 (u +2τ) dR R1 (u +2τ) dR θ1 R1 1 θ (θ ) θ (θ ) = dRdθ W 1 R − W 0 R R sin2 θ ZR0 ZR0 Zθ0 ZR0 Surfaces of Constant Mean Curvature in Homogeneous Three Manifolds with ] Emphasis in PSL2(R, τ) 131 which we can write in the form: θ1 (u +2τ) θ1 1 ∂ θ dθ =2H dθ θ W sin2 θ Zθ0 Zθ0 By considering that Ω is any domain in the plane Rθ, and taking the derivative with respect to ρ we obtain: u +2τ 2H ∂ θ = θ W sin2 θ by integrating this expression: u +2τ θ = 2H cot θ + d 2 2 2 2 1+4τ cos θ + sin θ(uθ +2τ) − where d R.p This implies: ∈ (u +2τ)2[1 sin2 θ(d 2H cot θ)2]=(d 2H cot θ)2[1+4τ 2 cos2 θ] θ − − − so the function u satisfies: (d 2H cot θ)√1+4τ 2 cos θ u(θ)= − dθ 2τθ 1 sin2 θ(d 2H cot θ)2 − Z − − p 8.2 Examples of surfaces invariant by one-parameter group of hyperbolic isometries in PSL2(R, τ) Now, we explore the Lemma 8.1.2.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    14 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us